Teknik Pengemasan dan Penyimpanan Virgin Coconut Oil (VCO) Yang Benar dan Halal Pada Produksi Skala Rumah Tangga - Putri, Elfia Siska Yasa; Wijiastuti, Wijiastuti; Setijanti, Herlina B. (Universitas Nusantara PGRI Kediri, 2021)
Women in the community in RT 03 Kekupu village, Depok wants to help the family finances by having a skill that can produce a product that can be sold. In this area, a lot of pineapples grow so the Community Service Faculty of Pharmacy and Science has taught the making of Virgin Coconut Oil (VCO) in the previous service. This service will continue with education on the correct and halal packaging, storage and critical points of Virgin Coconut Oil (VCO) products. The partners also obained a pocket book to assist them practice independently. They are interested in this activity because their new insights are inclined. Nearly 100% who attended the community service were very excited to join the program and they hope this activity will continue.